Brain and spinal cord paired stimulation coupled with locomotor training facilitates motor output in human spinal cord injury - Pulverenti, Timothy S.; Zaaya, Morad; Grabowski, Ewelina; Grabowski, Monika; Knikou, Maria (Frontiers in Neurology, 2022)
Combined interventions for neuromodulation leading to neurorecovery have gained great attention by researchers to resemble clinical rehabilitation approaches. In this randomized clinical trial, we established changes in the net output of motoneurons innervating multiple leg muscles during stepping when transcranial magnetic stimulation (TMS) of the primary motor cortex was paired with transcutaneous spinal (transspinal) stimulation over the thoracolumbar region during locomotor training. TMS was delivered before (TMS-transspinal) or after (transspinal-TMS) transspinal stimulation during the stance phase of the less impaired leg. Ten individuals with chronic incomplete or complete SCI received at least 20 sessions of training. Each session consisted of 240 paired stimuli delivered over 10-min blocks for 1 hour during robotic assisted step training on a motorized treadmill. Body weight support, leg guidance force and treadmill speed were adjusted based on each subject’s ability to step without knee buckling or toe dragging. Most transspinal evoked potentials (TEPs) recorded before and after each intervention from ankle and knee muscles during assisted stepping were modulated in a phase-dependent pattern. Transspinal-TMS and locomotor training affected motor neuron output of knee and ankle muscles with ankle TEPs to be modulated in a phase-dependent manner. TMS-transspinal and locomotor training increased motor neuron output for knee but not for ankle muscles. Our results support that targeted brain and spinal cord stimulation alters responsiveness of neurons over multiple spinal segments in people with chronic SCI. Noninvasive stimulation of the brain and spinal cord along with locomotor training is a novel neuromodulation method that can become a promising modality for rehabilitation in humans after SCI.